Jejak Kayu: Menggali Mitologi Jawa dalam Teknik Cetak Tinggi Kontemporer - Jimmy Ivan Suhendro; Tri Aru Wiratno; Walid Syarthowi Basmalah (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
The high printmaking technique is a printmaking method that involves creating prints with a carved surface to produce images in relief. This study explores the use of waste wood as a printing plate medium, which offers unique textures and motifs thanks to the varying wood grain, as well as the effects of burning, etching, and coloring. This study aims to demonstrate the novelty of the high printmaking technique by transforming the printing plate into a work of art itself, notjust a medium for printing images. The work is analyzed by identifying visual elements such as line shapes, colorcombinations, planes, spaces, and composition. Furthermore, this study adopts Javanese methodology in analyzingsymbols and stylization of forms, with Javanese mythological objects such as dragons, wayang puppets, and birds. The method used is artistic research, which utilizes artistic practice as a research tool to generate new knowledge. Primary data was collected through observation, documentation, and related journals. The results of this study demonstrate that the use of waste wood as a printing plate brings a new dimension to high printmaking, introducing artistic andphilosophical aspects that enrich the world of contemporary printmaking.